Study on Grounding System of the Metro Vehicles - Mingyuan HAO; Zhenliang FU; Xinghua WANG; Xueyan TIAN; Lijuan WANG (机车电传动)
The function of the grounding system is related to the operation performance of the metro vehicles, so it has special significance to conduct a research. The classification and definition of the vehicle grounding was introduced, including protective earthing, functional bonding and EMC-related grounding. The advantage and disadvantage of different earthing topology forms and the influence to the carbody current and EMC were analyzed by the circuit simulation and analysis methods, and vehicle grounding mode with grounding resistance decoupling function was recommended. For systems grounding, by comparing two different earthing methods of single-point and multiple-point, the latter was recommended.